1999
DOI: 10.2519/jospt.1999.29.10.609
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Water Volumetry and the Figure of Eight Method on Subjects With Ankle Joint Swelling

Abstract: Study Design: Single-group repeated measures with 2 raters. Objectives: To determine the interrater and intrarater reliability of water volumetry and the figure of eight method on subjects with ankle joint swelling. Background. Measurements of ankle swelling are commonly performed to determine the nature and stage of injury and to monitor progress made during rehabilitation. Water volumetry and the figure of eight method are 2 techniques used to measure ankle swelling. Methods and Measures: Twenty-nine subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 5 publications
2
73
1
Order By: Relevance
“…16,26,32 The high reliability of water-displacement volumetry observed in the current study is similar to that seen previously. 26 However, measurements in the current study were more variable with a range of average absolute differences between examiners of 5.1 mL to 71.9 mL. Petersen reported average differences of 11 mL to 18 mL.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…16,26,32 The high reliability of water-displacement volumetry observed in the current study is similar to that seen previously. 26 However, measurements in the current study were more variable with a range of average absolute differences between examiners of 5.1 mL to 71.9 mL. Petersen reported average differences of 11 mL to 18 mL.…”
Section: Discussionsupporting
confidence: 79%
“…While the figure-of-eight method has been shown to be a reliable measure in both healthy volunteers and volunteers with recent ankle injury, 14,16,26 reliability was inconsistent in the current study, with the agreement for the left ankle (ICC=0.86) much better than for the right ankle (ICC=0.64). In studies of healthy volunteers 14 and in patients with recent ankle or lower leg injuries, 16,26 reliability, as measured by the ICC, was 0.99.…”
Section: Discussionmentioning
confidence: 40%
See 2 more Smart Citations
“…In the hand, the volumeter has been found to be accurate to within 1% of the measured volume when used according to the manufacturer's directions. 23 Petersen et al 24 reported ICCs of .99 for interrater reliability and .98 to .99 for intrarater reliability for foot water volumetry. The water temperature was not measured but was considered cool (tap water).…”
Section: Tests and Measuresmentioning
confidence: 99%